Discovery of Phloeophagus Beetles as a Source of Pseudomonas Strains That Produce Potentially New Bioactive Substances and Description of Pseudomonas bohemica sp. nov. - Saati-Santamaría, Zaki; López-Mondéjar, Rubén; Jiménez-Gómez, Alejandro; Díez-Méndez, Alexandra; Větrovský, Tomáš; Igual, José M.; Velázquez, Encarna; Kolarik, Miroslav; Rivas, Raúl; García-Fraile, Paula (Frontiers in Microbiology, 2018)
Antimicrobial resistance is a worldwide problem that threatens the effectiveness of treatments for microbial infection. Consequently, it is essential to study unexplored niches that can serve for the isolation of new microbial strains able to produce antimicrobial compounds to develop new drugs. Bark beetles live in phloem of host trees and establish symbioses with microorganisms that provide them with nutrients. In addition, some of their associated bacteria play a role in the beetle protection by producing substances that inhibit antagonists. In this study the capacity of several bacterial strains, isolated from the bark beetles Ips acuminatus, Pityophthorus pityographus Cryphalus piceae and Pityogenes bidentatus, to produce antimicrobial compounds was analyzed. Several isolates exhibited the capacity to inhibit Gram-positive and Gram-negative bacteria, as well as fungi. The genome sequence analysis of three Pseudomonas isolates predicted the presence of several gene clusters implicated in the production of already described antimicrobials and moreover, the low similarity of some of these clusters with those previously described, suggests that they encode new undescribed substances, which may be useful for developing new antimicrobial agents. Moreover, these bacteria appear to have genetic machinery for producing antitumoral and antiviral substances. Finally, the strain IA19T showed to represent a new species of the genus Pseudomonas. The 16S rRNA gene sequence analysis showed that its most closely related species include Pseudomonas lutea, Pseudomonas graminis, Pseudomonas abietaniphila and Pseudomonas alkylphenolica, with 98.6, 98.5 98.4 and 98.4% identity, respectively. MLSA of the housekeeping genes gyrB, rpoB, and rpoD confirmed that strain IA19T clearly separates from its closest related species. Average nucleotide identity between strains IA19T and P. abietaniphila ATCC 700689T, P. graminis DSM 11363T, P. alkylphenolica KL28T and P. lutea DSM 17257T were 85.3, 80.2, 79.0 and 72.1%, respectively. Growth occurs at 4-37℃ and pH 6.5-8. Optimal growth occurs at 28ºC, pH 7–8 and up to 2.5% NaCl. Respiratory ubiquinones are Q9 (97%) and Q8 (3%). C16:0 and in summed feature 3 are the main fatty acids. Based on genotypic, phenotypic and chemotaxonomic characteristics, the description of Pseudomonas bohemica sp. nov. has been proposed. The type strain is IA19T (=CECT 9403T =LMG 30182T).